Shared Genetic Risk Factors Across Carbamazepine‐Induced Hypersensitivity Reactions. Issue 5 (3rd July 2019) - Nicoletti, Paola; Barrett, Sarah; McEvoy, Laurence; Daly, Ann K.; Aithal, Guruprasad; Lucena, M. Isabel; Andrade, Raul J.; Wadelius, Mia; Hallberg, Pär; Stephens, Camilla; Bjornsson, Einar S.; Friedmann, Peter; et al.
Abstract : Carbamazepine (CBZ) causes life‐threating T‐cell‐mediated hypersensitivity reactions, including serious cutaneous adverse reactions (SCARs) and drug‐induced liver injury (CBZ‐DILI). In order to evaluate shared or phenotype‐specific genetic predisposing factors for CBZ hypersensitivity reactions, we performed a meta‐analysis of two genomewide association studies (GWAS) on a total of 43 well‐phenotyped Northern and Southern European CBZ‐SCAR cases and 10, 701 population controls and a GWAS on 12 CBZ‐DILI cases and 8, 438 ethnically matched population controls. HLA‐A*31:01 was identified as the strongest genetic predisposing factor for both CBZ‐SCAR (odds ratio (OR) = 8.0; 95% CI 4.10–15.80; P  =   1.2 × 10 −9 ) and CBZ‐DILI (OR = 7.3; 95% CI 2.47–23.67; P  = 0.0004) in European populations. The association with HLA‐A*31:01 in patients with SCAR was mainly driven by hypersensitivity syndrome (OR = 12.9; P  = 2.1 × 10 −9 ) rather than by Stevens‐Johnson syndrome/toxic epidermal necrolysis cases, which showed an association with HLA‐B*57:01 . We also identified a novel risk locus mapping to ALK only for CBZ‐SCAR cases, which needs replication in additional cohorts and functional evaluation.